Colonic macrophage polarization in homeostasis, inflammation, and cancer - Isidro, Raymond A.; Appleyard, Caroline B. (American journal of physiology: Gastrointestinal and liver physiology, 2016)
Our review focuses on the colonic macrophage, a monocyte-derived, tissue-resident macrophage, and the role it plays in health and disease, specifically in inflammatory conditions such as inflammatory bowel disease and cancer of the colon and rectum. We give special emphasis to macrophage polarization, or phenotype, in these different states. We focus on macrophages because they are one of the most numerous leukocytes in the colon, and because they normally contribute to homeostasis through an anti-inflammatory phenotype. However, in conditions such as inflammatory bowel disease, proinflammatory macrophages are increased in the colon and have been linked to disease severity and progression. In colorectal cancer, tumor cells may employ anti-inflammatory macrophages to promote tumor growth and dissemination, whereas proinflammatory macrophages may antagonize tumor growth. Given the key roles that this cell type plays in homeostasis, inflammation, and cancer, the colonic macrophage is an intriguing therapeutic target. As such, potential macrophage-targeting strategies are discussed.